The Challenges of Implementing Project-Based Learning Models in Secondary Schools in Various Countries - Ridha Syahdia, Rizki; Nuryani, Harti; Nuryanti, Mira; Setya Sukmayani, Nuniek (Jurnal Edusci, 2024)
This article aims to describe the implementation of project-based learning models in various countries that can be used as a reference in learning in Indonesia. This study uses a qualitative approach with descriptive analysis. The data collection technique uses a literature review (study literature) made from books and scientific articles. The results of the study indicate that there are similarities in the implementation of project-based learning models in several countries consisting of the benefits and obstacles that occur. The benefits provided by the project-based learning model are that it can improve student learning outcomes, increase student enthusiasm and activeness in learning, and increase a sense of responsibility, teamwork, and independence in conducting learning. In addition to the benefits, several things become obstacles for teachers in implementing project-based learning models, namely limited time management, inadequate infrastructure, and the lack of teachers who have the competence to be able to carry out learning using project-based models.